Focus - Peels, H. G. L. 1956- (2022)
N.a.v.: Louis Stulman en Edward Silver, The Oxford Handbook of Jeremiah (New York: Oxford University Press, 2021) xix + 683 p., £ 97,00 (ISBN 9780190693060).
Keywords: Rezension